Molecular diagnosis of the gene responsible for the production of aflatoxin B1 produced by the fungus Aspergillus flavus (Journal of the College of Basic Education, 2022)
Aspergillusflavus is a highly toxic fungus that produces several types of mycotoxins. Aflatoxin B1 is the most toxic toxin and causes severe disease even at the lowest concentration below 10ppm. Diagnosing toxin production based on phenotypic and microstructural characteristics is unstable and subject to change under environmental conditions. Therefore, molecular and biological techniques such as polymerase chain reaction (PCR) are used to give an accurate diagnosis and to detect the genes responsible for aflatoxin biosynthesis. In this study, the aflatoxin B1 concentration was estimated using HPLC technique, the amount of toxin is related to the number of genes, and the detection of the gene responsible for AFB1 biosynthesis using polymerase chain reaction (PCR) based on the sequencing of the ITS regions crosses a reasonable means showing the genome of A. flavus and the aflatoxin synthesis gene afIR and this result can be used To better understand the genetic control of aflatoxin and reduce its risk.